Light Scattering in Solids IX Novel Materials and Techniques - Cardona, Manuel.; Cardona, Manuel.; Merlin, Roberto.; Merlin, Roberto. (Topics in Applied Physics,, 2007)
This is the ninth volume of a well-established series in which expert practitioners discuss topical aspects of light scattering in solids. It reviews recent developments concerning mainly semiconductor nanostructures and inelastic x-ray scattering, including both coherent time-domain and spontaneous scattering studies. In the past few years, light scattering has become one of the most important research and characterization methods for studying carbon nanotubes and semiconducting quantum dots, and a crucial tool for exploring the coupled exciton--photon system in semiconductor cavities. Among the novel techniques discussed in this volume are pump--probe ultrafast measurements and those which use synchrotron radiation as light source. The book addresses improvements in the intensity, beam quality and time synchronization of modern synchrotron sources, which made it possible to measure the phonon dispersion in very small samples and to determine electronic energy bands as well as enabling real-time observations of high-frequency sound propagation.